Instagram Sebagai Media Pemasaran Serenity Photoworks Dalam Menarik Minat Client - Misdiana, Raihan; Yusup, Eka; Poerana, Ana Fitriana (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Photography has become an integral part of our daily lives. The burgeoning interest in photography cannot be separated from the evolution of cameras over time. The advancement in camera technology has spurred the growth of the photography business. Serenity Photoworks is a service provider specializing in wedding photography, including pre-wedding, engagement, wedding, and other related events. One unique characteristic of Serenity Photoworks is its provision of on-site photo and video editing services, which are displayed during daytime receptions. This study aims to understand the advertising strategies used by Serenity Photoworks to attract clients. The method used is qualitative research with a constructivist paradigm and Integrated Marketing Communication (IMC). The subjects of this study consist of three informants: the owner, editor, and admin. Data collection techniques used include observation, interviews, and documentation.The results of the study show that Serenity Photoworks utilizes Instagram as its chosen advertising medium. Serenity Photoworks fully exploits Instagram features for promotional purposes and leverages Instagram ads.